SUDIRMAN ONLINE TRANSPORT HUB - Abi Rafi Pratama; Nina Carina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The advancement of the Transportation system goes hand in hand with the advancement of Technology. The ease of the need for public transportation can be easily accessed through smartphones, anywhere, and anytime so as to bring up the term Online Transportation. Online transportation is an internet-based transportation service in every transaction activity, ranging from booking, monitoring lines, payment, and assessment of the service. The impact of the progress of online-based public transportation can be both positive and negative. The positive impact is the ease of accessing public transportation anywhere and anytime. Another positive impact of online transportation is a fairly good level of comfort compared to conventional public transportation in terms of personal tracking, to help users in moving quickly. The negative impacts in the advancement of online-based public transportation are congestion caused by the buildup of online vehicles, friction between online pengemudi Transportasi onlines and conventional pengemudi Transportasi onlines and the use of the shoulder of the road that is used as points of customer waiting areas that cause the volume of roads to be limited and create congestion. Therefore, Sudirman Online Transportation Hub is present to organize their space or gathering points to be more organized and more organized movement and monitoring. Transport hub facility for online-based public transportation is a project created so that transportation, especially online-based ones no longer use the shoulder of the road for the gathering area, user waiting area and so on, so that the pengemudi Transportasi online and the user both have decent facilities to wait, pick up, and also rest. The facility also features many other supporting functions that are specially created so that they can be accessed using applications specifically designed for the project. Keywords: congestion; moving quickly; Transport hub facility; Online transportation AbstrakKemajuan sistem Transportasi berjalan beriringan dengan kemajuan Teknologi. Kemudahan kebutuhan akan transpotasi publik dapat dengan mudah di akses melalui smartphone, dimanapun, dan kapanpun sehingga memunculkan istilah Transportasi Online. Transportasi online adalah pelayanan jasa transportasi yang berbasis internet dalam setiap kegiatan transaksinya,mulai dari pemesanan,pemantauan jalur, pembayaran dan penilaian terhadap pelayanan jasa itu sendiri.  Dampak dari kemajuan Transportasi publik berbasis online dapat bersifat positif maupun negatif. Dampak positifnya adalah kemudahan dalam mengakses transportasi publik dimana pun dan kapan pun. Dampak Positif lain dari Transportasi online adalah tingkat kenyamanan yang cukup baik dibanding dengan transportasi publik konvensional dalam hal personal tracking, sehingga mampu membantu pengguna dalam berpindah tempat dengan cepat. Dampak negatif dalam kemajuan transportasi publik berbasis online adalah kemacetan yang disebabkan penumpukan kendaraan online, pergesekan antara pengemudi transportasi online dengan pengemudi Transportasi konvensional dan penggunaan bahu jalan yang dijadikan titik-titik area menunggu customer yang menyebabkan volume jalan menjadi terbatas dan membuat kemacetan. Untuk itu Sudirman Online Transport Hub hadir untuk mengatur ruang atau titik-titik berkumpul mereka supaya lebih tertata dan lebih teratur pergerakan dan pemantauannya. Fasilitas (Transport hub) untuk transportasi publik berbasis online ini merupakan  sebuah proyek yang dibuat agar transportasi khususnya yang berbasis online tidak lagi menggunakan bahu jalan untuk area berkumpul,area menunggu pengguna dan sebagainya, sehingga antara pengemudi dengan pengguna sama-sama memiliki fasilitas yang layak untuk menunggu, menjemput dan juga beristirahat. Fasilitas ini juga dilengkapi banyak fungsi pendukung lain yang dibuat khusus supaya dapat diakses menggunakan aplikasi yang dirancang khusus untuk proyek ini.